1983
DOI: 10.1029/jb088ib09p07495
|View full text |Cite
|
Sign up to set email alerts
|

Results from an absolute gravity survey in the United States

Abstract: Using the recently completed JILA absolute gravity meter, we made an absolute gravity survey which covered 12 sites in the United States. Over a period of 8 weeks, the instrument was driven a total distance of nearly 20,000 km to sites in California, New Mexico, Colorado, Wyoming, Maryland, and Massachusetts. The time spent in carrying out a measurement at a single location was typically 1 day. A measurement accuracy of around 1×10−7 m/s2 (10 μGal) is believed to have been obtained at each of the sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As of October l, 1989, the IGPP absolute gravity meter has occupied 22 sites in three countries, accumulating over 120,000 drops in 115 measurement sessions. Figure 2 presents gravity measurements at 12 sites in California; site descriptions may be found in the works by Zumberge et al [1983] and Zumberge et al [1986]. The data have not been corrected for environmental gravity signals other than the solid Earth tide.…”
Section: Results Of Absolute Gravity Surveys In Californiamentioning
confidence: 99%
See 1 more Smart Citation
“…As of October l, 1989, the IGPP absolute gravity meter has occupied 22 sites in three countries, accumulating over 120,000 drops in 115 measurement sessions. Figure 2 presents gravity measurements at 12 sites in California; site descriptions may be found in the works by Zumberge et al [1983] and Zumberge et al [1986]. The data have not been corrected for environmental gravity signals other than the solid Earth tide.…”
Section: Results Of Absolute Gravity Surveys In Californiamentioning
confidence: 99%
“…It will be shown that the environmental signals are not significant components of the g time series at station PFO, given the estimated experimental uncertainties. The time series data also include measurements made in 1982 with the Joint Institute for Laboratory Astrophysics (JILA) absolute gravity meter prototype [Zumberge et al, 1983]. Gravity values are all transferred to the floor, and the transfer uncertainty is included in the final uncertainty estimates.…”
Section: Results Of Absolute Gravity Surveys In Californiamentioning
confidence: 99%